Effects of Thermal Annealing on the Electrical Properties and Stability of Pt Thin Film Resistors with Ti and PtxOy Interlayers. Issue 1 (August 2021) - Pang, Yawen; Zhang, Congchun; Lei, Peng; Wang, Yusen; Lv, Zhenjie
Abstract: Influences of annealing temperature on microstructure, electrical properties, stability, and film adhesion of Pt thin film resistors with Ti interlayer and Ptx Oy interlayer were investigated and compared. Pt thin films were deposited on Al2 O3 substrates with Ti interlayer and Ptx Oy interlayer, respectively. Two resistors showed different microstructures after annealing. Pt/Ptx Oy film resistor owed more stable resistance value and larger temperature coefficient of resistance (TCR) than those of Pt/Ti film resistor. Annealed Pt/Ti film resistor exhibited poor stability than Pt/Ptx Oy film resistor and the stability became worse with increasing annealing temperature. In addition, the film adhesion of two resistors was discussed.